2011
DOI: 10.1177/0960327110388536
|View full text |Cite
|
Sign up to set email alerts
|

Decreased paraoxonase 1 activity and increased oxidative stress in low lead−exposed workers

Abstract: Paraoxonase 1 (PON1) has been proposed as an antioxidant enzyme. Although lead-inhibited PON1 activity has been demonstrated mostly based on in vitro experiments, it is uncertain whether this phenomenon is relevant in pathogenesis of lead-induced oxidative stress in the lead exposure. We examined associations of blood lead levels (BLL) and PON1 activity along with oxidative stress parameters in lead exposure workers. We determined malondialdehyde (MDA), conjugated diene (CD), total peroxides (TP), tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…One study measured the production of isoprostane to check the oxidation of tissue phospholipids and observed increased isoprostane levels in welders when compared with the control group; it also identifi ed that age and cigarette smoking did not contribute to the 2.4-fold increase in the isoprostane levels observed in welders (Han et al 2005 ). Two studies analyzed conjugated dienes, a primary end-product of LPO and both reported a positive correlation with BLLs (r = 0.33; p < 0.05 and r = 0.694; p < 0.001) (Permpongpaiboon et al 2011 ;Kasperczyk et al 2013c ).…”
Section: Lead-induced Oxidative Stress In Occupationally Exposed Popumentioning
confidence: 79%
See 1 more Smart Citation
“…One study measured the production of isoprostane to check the oxidation of tissue phospholipids and observed increased isoprostane levels in welders when compared with the control group; it also identifi ed that age and cigarette smoking did not contribute to the 2.4-fold increase in the isoprostane levels observed in welders (Han et al 2005 ). Two studies analyzed conjugated dienes, a primary end-product of LPO and both reported a positive correlation with BLLs (r = 0.33; p < 0.05 and r = 0.694; p < 0.001) (Permpongpaiboon et al 2011 ;Kasperczyk et al 2013c ).…”
Section: Lead-induced Oxidative Stress In Occupationally Exposed Popumentioning
confidence: 79%
“…Table 4 shows that MDA levels were the most frequently used biomarker for measuring LPO. Twenty studies found MDA levels to be signifi cantly higher in leadexposed groups (BLL, 5.4-317.3 μg/dL) than in the control groups (BLL, 0-12.5 μg/ dL) (Tenchova et al 1997 ;Ye et al 1999 ;Yucebilgiç et al 2003 ;Gurer-Orhan et al 2004 ;Kasperczyk et al 2004aKasperczyk et al , b , 2009Kasperczyk et al , 2013aOktem et al 2004 ;Patil et al 2006a , b ;Garçon et al 2007 ;Ergurhan-Ilhan et al 2008 ;Khan et al 2008 ;Mohammad et al 2008 ;Grover et al 2010 ;Permpongpaiboon et al 2011 ;Singh et al 2013 ). Among these, 15 studies reported a signifi cant positive correlation between BLLs and MDA concentrations ( r = 0.15-0.80; p < 0.05).…”
Section: Lead-induced Oxidative Stress In Occupationally Exposed Popumentioning
confidence: 96%
“…On the other hand, a positive association between Pb exposure and lipid peroxidation has been observed in studies with occupationally exposed adults (Bizon et al, 2013; Garcon et al, 2007; Garcia-Leston et al, 2012; Khan et al, 2008; Moro et al, 2010; Permpongpaiboon et al, 2011) and in few reports in the general adult population (Ahamed et al, 2009; Serafim et al, 2012). Most of the studies in occupationally exposed adults that assessed lipid peroxidation reported significant positive correlation between BLL and plasma MDA (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from experiments in animals and observational studies in occupationally-exposed adults suggest that exposure to high levels of Pb can induce the generation of lipid peroxidation products, alter the activities of antioxidant enzymes and cause changes to nucleic acid bases or structural damage to DNA molecules (Berrahal et al, 2011; Haleagrahara et al, 2011; Sandhir et al, 1995; Bizon et al, 2013; Garcon et al, 2007; Grover et al, 2010; Kasperczyk et al, 2012; Khan et al, 2008; Malekirad et al, 2010; Olewińska et al, 2010; Permpongpaiboon et al, 2011; Bizon et al, 2013; Garcon et al, 2004; Garcia-Leston et al, 2012; Khan et al, 2008; Moro et al, 2010; Permpongpaiboon et al, 2011). Further, among non-occupationally exposed non-pregnant US adults with low blood lead level (BLL), a positive association was reported between BLL and serum γ-glutamyltranferase (GGT), a liver enzyme and an early marker of OS, after adjusting for age, sex, race and socio-economic status (Lee et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…164 Oxidative stress resulting, for example, from strenuous physical activity, has been associated with decreased PON1 activity. [165][166][167] In contrast, regular, moderate physical activity has been shown to lower oxidative stress and improve lipoprotein metabolism including increasing HDL levels. The hypothesis that physical activity and oxidative stress can influence PON1 status has therefore been variously investigated.…”
Section: Diet and Lifestyle As Determinants Of Paraoxonase 1 Statusmentioning
confidence: 96%